Pelatihan Pembuatan Eco Enzym bagi Mahasiswa Baru STMIK Kaputama TA. 2024-2025 Sebagai Bentuk Kepedulian Kampus pada Pelestarian Lingkungan - Arliana, Lina; Maulita, Yani; Fauzi, Ahmad; Novriyenni, Novriyenni; Sihombing, Anton; Ambarita, Indah; Simanjuntak, Magdalena; Syahputra, Siswan; Khair, Husnul; Pramana, I Gusti; Annatasia, Kristina; Puspadini, Ratih; Selfira, Selfira; Sitompul, Melda Pita Uli; Khadafi, Muammar (Jurnal Pengabdian Pada Masyarakat METHABDI, 2025)
The growing volume of household organic waste poses a serious challenge to environmental sustainability. Through this community service program, STMIK Kaputama offers an educational and practical solution by involving first-year students in Eco Enzyme production training. Eco Enzyme, a fermented product derived from organic kitchen waste, has been proven to provide various benefits such as an eco-friendly cleaner, liquid fertilizer, and natural deodorizer, serving as an effective alternative to harmful chemical-based products. During the student orientation program (PKKMB), 300 students participated in a series of activities, including environmental education, fermentation practice, and harvesting of Eco Enzyme. The results demonstrated improvements in students’ knowledge and skills, with the expectation of long-term behavioral changes in managing waste at its source. The program successfully produced more than 300 liters of Eco Enzyme and significantly reduced organic waste disposal to landfills. More importantly, it cultivated environmentally conscious student leaders. Engaging first-year students in this real-world initiative serves as a strategic effort to instill sustainability values and foster a culture of environmental responsibility both within the campus and the broader community.